Prevalence of therapeutic drugs in blood of drivers involved in traffic crashes in the area of Bologna, Italy - Pelletti, Guido; Verstraete, Alain G.; Reyns, Tim; Barone, Rossella; Rossi, Francesca; Garagnani, Marco; Pelotti, Susi (Forensic science international, 2019)
•The prevalence of psychoactive drugs in the blood of Italian drivers was studied.•The highest prevalence was found for alcohol (17.3%), followed by medications (13.6%).•The prevalence of Benzodiazepines (7.3%) was much higher than in previous studies.•Antidepressants/antipsychotics and medical opioids had a prevalence of 7.2% and 3.1%.•Medications were mostly found in females and in drivers older than 60-year-old. Psychoactive medicines, such as benzodiazepines and Z-drugs (BdZ), antidepressants and antipsychotics (AA) and medical opioids (MO), have an impairing effect on driving ability. In previous epidemiological studies performed on impaired and/or injured drivers, not all relevant psychoactive substances were included in the toxicological assessment, and their prevalence may be underestimated. This study aims to assess the prevalence of a large set of psychoactive substances (n=53) in Italian drivers involved in a road traffic crash and in predefined population subgroups. The toxicological analyses were performed on the whole blood of 1026 drivers involved in a road traffic crash in the area of Bologna, Italy, from January 2017 to March 2018. Analyses were performed using GC-FID (alcohol), GCMS (illicit drugs) and LC/HRMS (psychoactive drugs). The population was divided into subgroups according to gender, age and crash time. Descriptive statistics were used in order to assess differences among sub-groups. The highest prevalence was found for alcohol (17.3%), followed by medicinal drugs (13.6%) and illicit drugs (5.5%). The prevalence of BdZ, AA and MO were 7.3%, 7.2% and 3.1%, respectively. The frequency of BDZ and AA was significantly higher in female drivers and showed higher prevalence at increasing age. The presence of medicinal drugs was significantly higher during the week and in crashes occurring during the day. Results for alcohol and illicit drugs partially overlap with those reported in previous European and Italian studies, but the prevalence of BdZ was much higher. We also found a high prevalence of AA, which are rarely investigated in epidemiological studies performed on drivers, but may cause impairment of the ability to drive, especially when taken in combination with alcohol or other drugs. The pattern of medication use differs from that involving drugs of abuse, since it is mainly observed in female subjects and older drivers and does not follow the same weekly trend observed for alcohol and other illicit drugs.